Numerical Study on the Behavior of Square Stiffened Caissons Penetrating into Normally Consolidated Clay - Wei Liu; Zhihuai Huang; Mi Zhou (Advances in Civil Engineering)
Significant difference between predicted and measured installation resistance of stiffened suction caissons was identified due to the existing uncertainty regarding the mobilized soil flow mechanisms. This paper describes an extensive investigation of square stiffened caisson penetration in nonhomogeneous clays undertaken through large deformation FE (LDFE) analysis to identify the soil flow mechanisms around and between lateral ring stiffeners. A detailed parametric study has been carried out, exploring a range of nondimensional parameters related to stiffened caisson geometry, caisson roughness, and soil strength. The LDFE results were compared with centrifuge test data in terms of soil flow mechanisms, with good agreement obtained. Two interesting features of soil flow inside the caisson were observed including soil backflow into the gaps between the embedded stiffeners and soil heaving at the surface. It shows that the cavity depth can reach ∼5 m. Finally, simple expressions were proposed for estimating the critical depths of soil backflow and cavity formation.